Comparative evaluation of physical characteristics of different inflatable penile prostheses. (3rd September 2017) - Barboglio Romo, Paholo; Chikkatur, Harshitha Prakash; Beldona, Sahana; Yi, Yooni; Bruns, Tim M.; Malaeb, Bahaa S.
Abstract: Objective: The aim of this study was to describe and evaluate existing inflatable penile prostheses (IPPs) in an independent laboratory setting. Materials and methods: New IPPs were obtained from two manufacturers: American Medical Systems (AMS) and Coloplast. The AMS 700™ LGX (18 cm), CX (18 cm) and CXR (14 cm), and the Coloplast Titan ® Touch (18 cm) and Titan Narrow (14 cm) were investigated. Internal pressure, length and girth of the cylinders were measured at 2 ml increments. A urodynamic individual transducer connected to an analogue amplifier and recording system was used to measure pressure. Rigidity and axial loading of the different IPPs were evaluated with a compression system. Results: Regular-size prostheses were inflated to 22 ml and narrow prostheses to 16 ml. The Titan Touch had a girth of 17.8 mm at 22 ml compared to 15.6 mm for the AMS 700 LGX and 16.5 mm for CX. The AMS 700 LGX increased in length by 13 mm from baseline, a feature that was unique among all the tested prostheses. Rigidity curves as assessed by compression showed significant variability, with both Titan prostheses and the AMS CXR exhibiting similar patterns and requiring a higher load to reach 50% compression. The buckling experiment showed different patterns of deformity. Conclusions: The results suggest that these prostheses exhibit significant physical differences. The clinical impact of these differences is poorly elucidated. These variations in behavior of the prostheses could be considered by physicians and patients when objectively assessing the choice of prosthesis. These findings could aid in objective patient counseling.